Pengaruh Deskripsi Pekerjaan, Kepemimpinan dan Insentif Terhadap Kinerja Karyawan Pada Lembaga Pendidikan dan Pelatihan Aparatur Negara (LPPAN) di Kota Palembang - Salsabilah, Putri; Fitriana, Nina; Hasanah, Umi (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to determine whether there is an Influence of Job Description, Leadership and Incentives on Employee Performance at the State Apparatus Education and Training Institution (LPPAN) in Palembang City. The population and sample of this study were 35 people. The analysis technique used was multiple linear regression analysis which was processed using the assistance of the Statistical Product and Service Solution (SPSS) version 26 computer program. The results of the study indicate that there is an influence of Job Description, Leadership and Incentives on Employee Performance at the State Apparatus Education and Training Institution (LPPAN) in Palembang City. With a significance of 0.000 <0.05. There is a simultaneous influence between Job Description, Leadership and Incentives on Employee Performance at the State Apparatus Education and Training Institution (LPPAN) in Palembang City. There is a partial influence between Job Description on Employee Performance at the State Apparatus Education and Training Institution (LPPAN) in Palembang City. There is no partial influence between Leadership on Employee Performance at the State Apparatus Education and Training Institution (LPPAN) in Palembang City. There is no partial influence between Incentives on Employee Performance at the State Apparatus Education and Training Institution (LPPAN) in Palembang City.